SOA based mobile application software test framework - Zhi-fang Liu; Bin Liu; Xiao-peng Gao (2009 8th International Conference on Reliability, Maintainability and Safety, 2009)
The most important issues of the test framework are its generality, reusability and scalability in a specific area. Mobile application software that constantly updates and improves makes it especially difficult for these points. This paper first proposes the definition of mobile application software, as well as its classification, and summarizes the mobile application software testing technology. Then we introduce the thought of service-oriented architecture into this area, and adopt COM technique, aims at designing a mobile application software test framework. During the design, we focus on the technical implementation and interface definition. Finally a test platform is built based on the framework and used to test a typical software of mobile phone. The test results show that the test framework greatly improved the testing flexibility and provided a good foundation for implementation and expansion of mobile application test.